2008
DOI: 10.1108/09596110810873499
|View full text |Cite
|
Sign up to set email alerts
|

Online distribution strategies and competition: are the global hotel companies getting it right?

Abstract: Purpose -The internet has significantly changed the ways hotels distribute and price their products. The imminent success of online intermediaries caused financial problems for hotel chains since online travel agencies offered better prices than the hotel brand websites. The existing literature on hotel online distribution has focused on pricing strategies and room availability issues for different segments of hotels. This paper, however, aims to compare online room prices of global hotel chains across online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 27 publications
4
65
0
Order By: Relevance
“…Findings in terms of product distribution in this research resonated with the literature in terms of main distribution channel usage, cost of distribution, and rate parity issues (Choi and Kimes, 2002;Mainzer, 2004;Gazolli et al, 2008;Vinod, 2009;Mourier, 2010). The emerging of social media was noted in the Prague Hiltons, but not to the extent that Carroll and Noden (2010) mention.…”
Section: Resultssupporting
confidence: 56%
“…Findings in terms of product distribution in this research resonated with the literature in terms of main distribution channel usage, cost of distribution, and rate parity issues (Choi and Kimes, 2002;Mainzer, 2004;Gazolli et al, 2008;Vinod, 2009;Mourier, 2010). The emerging of social media was noted in the Prague Hiltons, but not to the extent that Carroll and Noden (2010) mention.…”
Section: Resultssupporting
confidence: 56%
“…Demirciftci et al (2010), and G. Gazzoli et al (2008) found that in the developed hotel market in the United States, distribution channels are not used as a common tool of price differentiation. Thus, there are no significant differences between prices of accommodation facilities offered in direct and indirect online distribution channels.…”
Section: Internetization and The Relations Between Hotel Industry Andmentioning
confidence: 99%
“…Using various business practices, online travel agents were able to provide lower prices than the rates offered by the hotels on their own websites. As the result, irrespective of price parity or disparity, hotel guests looking for a better offer are used to employing search engines of various intermediaries and reading the content of plenty of hotels' own websites (Gazzoli et al, 2008).…”
Section: Internetization and The Relations Between Hotel Industry Andmentioning
confidence: 99%
“…Considering both perspectives, one interpretation is that the effective adoption of RMO in the hotel trade hinges on the perceived trade-off between long-term performance and short-term objectives, since the short-term profit objectives prevalent in the industry may be inconsistent with the understanding that the lifetime value inherent to relational exchanges can take considerable time to realise a payoff (Tse et al, 2004;Wang, 2012). That is, while RMO may be perceived as widely adopted in the hotel industry, situations of poor business performance, as illustrated by OTAs putting competitive pressure on hotel room rates and eroding both hotel-room income and -customer allegiance (Christodoulidou et al, 2007;Gazzoli et al, 2008;Murphy et al, 2005;Rohlfs and Kimes, 2007;Tso and Law, 2005), suggest that failure to achieve effective performance outcomes needs examining, in order to improve the quality of management information, hence enabling better decision-making. Indeed, failure might be explained by a short-term profit orientation, implementation inefficiencies and inconsistencies that may characterise the impact of cost minimisation fostered by competitive pressure.…”
Section: Summary Further Research and Limitationsmentioning
confidence: 99%